Abemaciclib for the treatment of HR+/HER2- breast cancer. Issue 3 (4th May 2018) - Exman, Pedro; Tolaney, Sara M.
ABSTRACT: Introduction : More than 70% of patients with advanced breast cancer have hormone receptor (HR)-positive disease and almost all patients will develop resistance to endocrine agents and experience disease progression. CDK 4/6 inhibitors represent a new paradigm shift in treatment for patients with endocrine resistance. Also, its use as front-line therapy reached unprecedented progression-free survival rates in these patients. Currently, there are 3 CDK 4/6 inhibitors available: ribociclib, palbociclib and abemaciclib. Areas covered : In this review, the authors analyze abemaciclib from its pre-clinical development until recent randomized phase III trials, which led to the approval and use of this extremely relevant drug in the treatment of HR-positive breast cancer. The authors also discuss abemaciclib's different adverse events profile compared to similar drugs and its potential role as monotherapy and as treatment for brain metastasis. Expert commentary : Abemaciclib is an important advance in the treatment of metastatic HR-positive/HER2-negative breast cancer, and data support its use in combination with endocrine therapy for first- and second-line therapy for metastatic disease, and its unique efficacy as monotherapy and for CNS metastasis. Molecular biomarkers, combination therapy with other agents, and the best sequence for treatment are under investigation and should clarify how to optimize treatment for each patient.